Associations between omega-6 polyunsaturated fatty acids, hyperinsulinemia and incident diabetes by race/ethnicity: The Multi-Ethnic Study of Atherosclerosis. Issue 10 (October 2020) - Weir, Natalie L.; Nomura, Sarah O.; Steffen, Brian T.; Guan, Weihua; Karger, Amy B.; Klein, Ronald; Klein, Barbara E.K.; Cotch, Mary Frances; Tsai, Michael Y.
Summary: Background & aims: Omega-6 polyunsaturated fatty acids (PUFAs) have been shown to relate to insulin resistance and type 2 diabetes (T2D), but influence of race/ethnicity has not been investigated. The aim of this study was to determine whether omega-6 PUFAs, and estimated desaturase enzyme activity, are associated with fasting glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR) and incident T2D, and whether associations differ by race/ethnicity. Methods: This study was conducted in the Multi-Ethnic Study of Atherosclerosis (MESA) (N = 6282). Associations between baseline plasma phospholipid fatty acids (LA, Linoleic Acid; GLA, γ-linoleic acid; DGLA, Dihomo-γ-linolenic acid; AA, arachidonic acid; D5D, delta-5 desaturase; D6D, delta-6 desaturase), fasting glucose, insulin, and HOMA-IR [(fasting insulin – fasting glucose)/22.5] were evaluated using linear regression. Associations between omega-6 PUFAs (N = 5508 after excluding diabetics at baseline) and T2D incidence were assessed using Cox proportional hazards regression. Analyses were replicated/stratified by race/ethnicity (White, Black, Chinese, Hispanic) and tests for interaction were assessed by inclusion of a cross-product term in models. Results: In fully adjusted models, insulin and HOMA-IR were positively associated with LA (insulin: 0.213 per SD, p = 0.01; HOMA-IR: 0.252 per SD, p < 0.001), GLA (insulin: 0.010 per SD, p < 0.001; HOMA-IR: 0.006 per SD, p < 0.001), DGLA (insulin: 0.279 per SD, p < 0.001; HOMA-IR: 0.175 per SD, p < 0.001) and D6D activity (insulin: 0.001 per SD, p < 0.001; HOMA-IR: 0.006 per SD, p < 0.001), and inversely associated with AA (insulin −0.272 per SD, p < 0.001; HOMA-IR: −0.125 per SD, p = 0.03) and D5D activity (insulin: −0.530 per SD, p < 0.001; HOMA-IR: −0.322 per SD, p < 0.001), while weak or no associations were observed with fasting glucose, and associations appeared to differ by race/ethnicity. After accounting for HOMA-IR at baseline, LA was inversely (HR: 0.87, p = 0.003) and DGLA (HR: 1.17, p < 0.001) and AA (HR: 1.15, p = 0.001) were positively associated with T2D in the overall population, but associations were attenuated or no longer present when stratified by race/ethnicity (P-interaction >0.05). Conclusions: Results confirm previous reports that omega-6 PUFAs are associated with hyperinsulinemia. Findings suggest omega-6 PUFAs are more likely markers of hyperinsulinemia rather than a protective/risk factor for T2D and indicate racial/ethnic differences in associations, but further research is needed to confirm findings.